2009
DOI: 10.1007/s12015-009-9050-8
|View full text |Cite
|
Sign up to set email alerts
|

Pre-transplantation Specification of Stem Cells to Cardiac Lineage for Regeneration of Cardiac Tissue

Abstract: Myocardial infarction (MI) is a lead cause of mortality in the Western world. Treatment of acute MI is focused on restoration of antegrade flow which inhibits further tissue loss, but does not restore function to damaged tissue. Chronic therapy for injured myocardial tissue involves medical therapy that attempts to minimize pathologic remodeling of the heart. End stage therapy for chronic heart failure (CHF) involves inotropic therapy to increase surviving cardiac myocyte function or mechanical augmentation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 116 publications
0
10
0
1
Order By: Relevance
“…Moreover, transplantation methods and post-transplantation efficiency of these cells need to be better improved, due to their poor survival, the reduced engraftment potential, and the safety issues. As reviewed in literature, the drug or hypoxic preconditioning of stem cells populations, in addition with growth factor cocktails, resulted in an upregulation of all those factors involved in survival, migration, myocardial tolerance, and possible differentiation towards a cardiac fate [43,44].…”
Section: Embryonic Stem Cells and Induced Pluripotent Stem Cellsmentioning
confidence: 99%
“…Moreover, transplantation methods and post-transplantation efficiency of these cells need to be better improved, due to their poor survival, the reduced engraftment potential, and the safety issues. As reviewed in literature, the drug or hypoxic preconditioning of stem cells populations, in addition with growth factor cocktails, resulted in an upregulation of all those factors involved in survival, migration, myocardial tolerance, and possible differentiation towards a cardiac fate [43,44].…”
Section: Embryonic Stem Cells and Induced Pluripotent Stem Cellsmentioning
confidence: 99%
“…These cKit+/CD45− cells have been shown 8 to have cardiogenic potential, both in-vitro and in-vivo. There are numerous varieties of putative cardiac precursor cells 1012 , but their roles in the normal physiology of the heart, or their ability and capacity for cardiac repair after injury is still not well known, especially in large animals and humans 13 . This topic is clearly of clinical relevance since human heart disease that culminates in cardiac performance deficits is largely the result of the loss of contractile cardiocytes, such as after a myocardial infarction 14, 15 .…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, different approaches can be used, such as gene therapy to over-express transcription factors, and modulation of crucial pathways by cocktails of cytokines and growth factors, small molecules, miRNA or modified RNAs [1]. Furthermore it has been observed that exposure of CSps and CDCs to extremely low-frequency electromagnetic fields (ELF-EMFs), tuned at Ca 2+ ion cyclotron energy resonance (Ca 2+ -ICR), modulates their differentiation, turning on cardiogenesis and turning off vasculogenesis, without any pharmacological or genetic manipulation [94].…”
Section: Ex Vivo Treatments On Injected Cellsmentioning
confidence: 99%
“…Current treatments provide limited benefits and amelioration of symptoms, but they do not recover the function of the damaged tissue. Treatment of acute myocardial infarction (AMI) is focused on restoring the ante-grade flow in order to inhibit further tissue loss, while chronic therapy for injured tissue is aimed at minimizing pathologic remodeling of the heart, and endstage therapy for chronic heart failure (CHF) is based on inotropic drugs to improve the function of surviving cardiomyocytes and/or their mechanical performance [1]. The only routinely used therapeutic approach to replace the injured tissue is heart transplantation, which is a last chance treatment, given the limited donor pool [2].…”
Section: Introductionmentioning
confidence: 99%